Trade in value added: Do we need new measures of competitiveness? - Kirsten Lommatzsch; Maria A. Silgoner; Paul Ramskogler (Deutsche Bundesbank, 2016)
It has been argued that the increasing importance of global value chains necessitates a modification of conventional competitiveness measures. We compile a broad dataset including value added trade, gross exports and conventional and value added based real exchange rates. To sharply focus on external competitiveness, a new price competitiveness indicator is introduced, the TWULC (Trade Weighted Unit Labour Cost indicator). It weights sectorspecific cost trends according to sector shares in exports. Econometric tests for a panel of 38 countries show that the focus on value added trade generally improves the explanatory power of export equations. Value added exports' sensitivity towards real exchange rates is up to four times higher than that of gross exports. Real effective exchange rates focusing on exporting industries and on value added weights yield more robust results across the specifications, but do not systematically outperform the more conventional measures of price or cost competitiveness.
Keywords: F14; J30; 330; competitiveness; external trade; labour costs